HUBUNGAN STRES DENGAN KEKAMBUHAN ASMA PADA PENDERITA ASMA BRONKIAL DI WILAYAH KERJA UPT PUSKESMAS BOTANIA KOTA BATAM - Halimatusyakdiah, Nur; Gemini, Savitri; Yunaspi, Didi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract : Bronchial asthma affects about 300 million people worldwide. In Indonesia, asthma is the first non-communicable chronic disease with a total of 14.5 million and is the cause of morbidity and mortality. In Batam, bronchial asthma patients reached 2,281 people. Recurrence of bronchial asthma is caused by several factors, one of which is stress. This study aims to determine the relationship between stress and asthma recurrence in patients with bronchial asthma in the UPT Puskesmas Botania Working Area in Batam 2023. This research design uses case control. Respondents in this study were 42 cases and 42 controls. The sampling technique used is Non-probability Sampling, namely Systematic Sampling. The Chi-Square test results show (P-value 0.006 OR 8.357) so that Ho is rejected and Ha is accepted. So it can be concluded that there is a relationship between stress and asthma recurrence in patients with bronchial asthma in the UPT Puskesmas Botania Working Area in Batam 2023 and with an OR value of 8.357, which means that asthma sufferers who have stress are at risk of experiencing asthma recurrence 8.357 times, compared to asthma sufferers who are not stressed. The results of this study can be used as information, reference and can motivate bronchial asthma patients to always pay attention to their health and are expected to stay away from factors that cause recurrence of bronchial asthma, especially being able to control stress so that asthma is controlled and does not relapse frequently.Keywords: Bronchial Asthma, Stress, Recurrence